Five new records of marine shrimps (Decapoda: Caridea, Stenopodidea) from the Caribbean coast of Panama - Pachelle, Paulo P.g.; Leray, Matthieu; Anker, Arthur; Lasley, Robert (Zootaxa, 2018)
Five species of shrimps, four carideans and one stenopodidean, are recorded for the first time from the Caribbean coast of Panama: Lysmata vittata (Stimpson, 1860) [Lysmatidae Dana, 1852], Periclimenaeus ascidiarum Holthuis, 1951, P. bredini Chace, 1972, P. maxillulidens (Schmitt, 1936) [Palaemonidae Rafinesque, 1815], and Odontozona edyli Criales & Lemaitre, 2017 [Stenopodidae Claus, 1872]. Rather surprisingly, L. vittata is recorded from the Caribbean Sea for the first time. However, the taxonomic status of all western Atlantic specimens currently assigned to L. vittata (including the Panamanian material and the Brazilian L. rauli Laubenheimer & Rhyne, 2010) will need a much more careful reassessment, which will only be possible after determining the taxonomic identity of L. vittata in the Indo-West Pacific. The colour patterns of P. ascidiarum, P. bredini and O. edyli, herein illustrated for the first time, appear to be species-diagnostic and may serve as additional important taxonomic characters. For O. edyli, the previously unknown thoracic sternum of the female is illustrated, as well as the variation in the rostral dentition.